The Role of Socioeconomic Status, School Climate, and Technology Use in Predicting Emotional Well-being and Learning Satisfaction of Indonesian Teenagers - Maghfiroh, Nasruliyah Hikmatul (Westscience Press, 2025)
This study investigates the role of socioeconomic status, school climate, and technology use as predictors of emotional well-being and learning satisfaction of Indonesian teenagers. Based on quantitative research, data were collected from 250 participants and analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results show that the independent variables of socioeconomic status, school climate, and technology utilization are disproportionately contributing to emotional well-being and satisfaction with learning. Emotional well-being is acting as a central mediator, enhancing the salutary effects of the independent variables on satisfaction with learning. These results stress the importance of aiming at socioeconomic disparities, creating healthy school environments, and adopting balanced use of technology in learning. The study provides policy guidelines to policymakers and educators to enhance the emotional and academic outcomes of Indonesian adolescents.